ARGUMENTATION OF ECOLOGICAL MONITORING SYSTEMS OF MІD-SIZED CITIES - Klуmenko, Liudmyla (Вісник Національного університету водного господарства та природокористування. Серія «Сільськогосподарські науки», 2020)
Analysis of statistic data which characterize ecological state of urban ecosystems has been done. On its basis the local system of ecological monitoring of the cities, taking into account own experience and the experience of EU countries, has been worked out. It includes the following moduls: emission into atmospheric air, water consumption, the state of soils, waste products, treatment, the state of green plantation. Ambient air monitoring means the information-mechanical system of observing the estimation and prediction of the level of atmospheric air pollution (gases, particles of solids or liquids) and providing with recommendations on atmospheric air proteсtion measures on this basis. Surface water monitoring refers to a system of consistent periodical observations, collection, processing and accumulation and storage of information on the state of water areas, the prognostication of possible changes in water quality, and the development of recommendations and proposals for management decisions to maintain or improve their state. Soil monitoring objects are basic soil types, subtypes, types and varieties. Soil state is reliably diagnosed with information on their composition. The ecological state of soils is evaluated depending on the change of their norms by the following conditions: satisfactory (or zone of ecological norm); conditionally satisfactory (risk area); unsatisfactory (crisis zone); catastrophic (disaster zone). The main indicator characterizing the state of green spaces in cities is the indicator of the level of city landscaping, which is estimated in m2 per person. The state of green space can be assessed by changes in leaves of the trees, changes in color, the presence of necrosis, the beginning of deformation, the presence of expressed bilateral asymmetry.